ON THE IMPACT OF THE INDIAN-PAKISTANI CONFRONTATION ON SITUATION IN SOUTH ASIA - Ikhtiandr Uvraimov; Obidjonova Mohira (Modern American Journals, 2025)
This article analyses the India-Pakistan conflict as one of the most enduring and complex aspects of South Asia, shaped by the rise of British India in 1947 and the enshrined dispute over the status of Jammu and Kashmir. The article examines the historical, political and strategic background of the conflict, its impact on regional security and the formation of sustainable strategic instability, including in the context of nuclear deterrence. It concludes that the India-Pakistan conflict remains a key obstacle to regional cooperation and integration in South Asia.
Keywords: India-Pakistan conflict, South Asia, regional security, Jammu and Kashmir, nuclear deterrence, strategic instability, unstable deterrence, terrorism, SAARC, international actors, crisis, arms control.